PERFORATED APPENDIX: CONTRIBUTING FACTORS - Tanveer Ahmad; Zulfiqar Ali (Journal of University Medical & Dental College)
ABSTRACT Objectives: Study the various risk factors contributing in perforation of appendix and improve our management of patients by early detection of risk factors. Materials and methods: This is a simple descriptive study and was conducted in the Surgical Unit Madina Teaching Hospital during the period from January 2008 to June 2010. Patients of all ages and both sexes operated for appendicitis were included in the study. The history, clinical features, investigations and operative findings were noted and recorded on the standard proforma. Surgical procedures performed and complications were recorded and managed accordingly. Results: The incidence of perforated appendicitis is higher in males (69.17%) as compared to females (30.82%). The incidence of perforated appendicitis is higher in the extreme of ages. In the first decade it is 46.15% and in the elderly it is 56.61% of the patients presenting with appendicitis. The mean delay from the onset of symptoms to surgery for perforated appendix is 4.2 days. Most of the patients (60.90%) were admitted with complaints of pain right iliac fossa with fever. 27 patients (20.30%) operated for perforated appendicitis presented with generalized peritonitis. The obstructive appendicitis due to faecolith is strongly associated with the perforated appendicitis. The patients with diabetes have more incidence of perforation of the appendix. Similarly, the incidence of perforation of appendix is higher in patients who are taking steroid therapy. The most common postoperative complications after appendicectomy for perforated appendicitis were fever (33.83%) and wound infection (30.07%). Conclusions: Perforated appendicitis is associated with high morbidity and mortality rates especially in children, elders, pregnant woman, diabetics, steroid dependent and immunocompromised patients. We should be aggressive in the treatment of appendicitis in the high risk patients. So once acute appendicitis is diagnosed, the expedient surgery and appropriate use of perioperative antibiotics can help to minimize the morbidity and mortality.